RISYWAH DALAM TINJAUAN HUKUM ISLAM DAN UNDANG-UNDANG TINDAK PIDANA SUAP - Bahagia, Bahagia (JURNAL ILMU SYARIAH, 2013)
The behavior of consuming illicit wealth by way of bribes (rasywah) is already entrenched in the middle of the Indonesian people and the world community in general. That is why since the beginning of Islam came Messenger of Allah has warned Muslims to acquire wealth through legal means. Accepting bribes or kickbacks is a very nasty behavior, because there are hidden fraudulent behavior committed to achieve a certain goal. In Indonesia bribery act categorized as acts of corruption punishable by imprisonment.